Soil-transmitted helminths associated with BMI in schoolchildren of Chakdara, Lower Dir, Pakistan (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: This study aimed to determine the association between soil-transmitted helminths and body mass index (BMI) among the school children of Chakdara, Lower Dir, Pakistan. Materials and Methods: Students aged 5–15 years participated in this study. Stool specimens were collected from 130 students between August 2020 and September 2021 and examined both macroscopically and microscopically. The height and weight were measured, then classified as normal BMI or underweight BMI according to the World Health Organization range criteria. Results: The overall prevalence was noted as 38.5%, with 35.9% of males and 43.9% of females being infected. Roundworms (56%) were the most prevalent, followed by hookworms (28%) and whipworms (16%). Students with 5–8 years of experience presented the highest prevalence rate of 41.2%, followed by those with 9–12 years (33.3%) and 13–15 years (40%). A total of 30% of children had a normal BMI, while 70% were underweight. Of the 38.5% of infected children, 26% had a normal BMI, while 74% were underweight. Lack of handwashing with soap, lack of footwear, and low family income were identified as significant risk factors (p-value < 0.05) for helminth infection, while other factors, such as family size and access to a toilet at home, showed no significant association (p-value = 0.05). The association between soil-transmitted helminths (STH) infection and underweight BMI (p-value = 0.20) even though a sizable portion of students possessed BMIs, heights, and weights below standard reference ranges. Conclusion: The present study concludes that being underweight is a risk factor for STH infection, reflecting poor hygiene standards and malnutrition in children. To reduce infection rates, these children must adopt a better diet and practice better personal, environmental, and hygiene habits.J. Adv. Vet. Anim. Res., 12(4): 1228–1236, December 2025http://doi.org/10.5455/javar.2025.l983